KODA score: an updated and validated bowel preparation scale for patients undergoing small bowel capsule endoscopy - Alageeli, Mohammad; Yan, Brian; Alshankiti, Suliman; Al-Zahrani, May; Bahreini, Zoya; Dang, ThucNhi T.; Friedland, Joshua; Gilani, Syed; Homenauth, Ravi; Houle, Jennifer; Kloc, Milica; Luhoway, Jacqueline; Merotto, Lucas; Rofaiel, Rymon; Singh, Chantal; Smith, Alexis; Thomas, Benson; Townsend, Cassandra; Yoo, David; Zepeda-Gomez, Sergio; Stitt, Larry; Jairath, Vipul; Sey, Michael Sai Lai (Endoscopy International Open, 2020)
Background and study aims A reliable outcome measure is needed for bowel preparation quality during capsule endoscopy. Currently, no scales are adequately validated. Our objective was to update an existing small bowel preparation score, create a standardized training module, then determine its inter-rater and intra-rater reliability. Patients and methods Modification to produce standardized scoring of an existing small bowel preparation score was performed followed by development of a training module and validation to create the new Korea-Canada (KODA) score. Twenty readers from a range of backgrounds, including capsule endoscopists, gastroenterology fellows, residents, medical students, and nurses rated bowel cleanliness in 25 capsule videos consisting of 1,233 images, in duplicate 4 weeks apart, after completing the training module. Sequential images selected in 5-minute intervals during small bowel transit were rated on a scale between 0–3 based on the amount of visualized mucosa and the degree of obstruction. Reliability was assessed using estimates of intraclass correlation coefficients (ICCs). Results Intraclass correlation coefficients for inter-rater (ICC 0.81, 95 % CI 0.70–0.87) and intra-rater (ICC 0.92, 95 % CI 0.87–0.94) reliability were almost perfect among the 20 readers. Inter-rater reliability ranged between 0.72 (95 % CI 0.57–0.81) and 0.89 (95 % CI 0.79–0.93) for nurses and residents, respectively. Intra-rater reliability was greater than 0.90 for all groups except for nurses, which was still almost perfect (ICC 0.86, 95 % CI 0.79–0.90). Conclusions Almost perfect inter-rater and intra-rater reliability was observed for the KODA score. This simple score could be used for future clinical trials after completion of the training module.